Higher TNF-α, IGF-1, and Leptin Levels are Found in Tasters than Non-Tasters - Wang, Rui; van Keeken, Nika M. A.; Siddiqui, Sana; Dijksman, Lea M.; Maudsley, Stuart; Derval, Diana; van Dam, P. Sytze; Martin, Bronwen (Frontiers in Endocrinology, 2014)
Taste perception is controlled by taste cells that are present in the tongue and produce and secrete various metabolic hormones. Recent studies have demonstrated that taste receptors in tongue, gut and the pancreas are associated with local hormone secretion. The aim of this study was to determine whether there is a link between taste sensitivity and levels of circulating metabolic hormones in human and whether taste sensitivity is potentially related to peripheral metabolic regulation. 31 subjects were recruited and separated into tasters and non-tasters based on their phenol thiocarbamide (PTC) bitter taste test results. Fasting plasma and saliva were collected and levels of hormones and cytokines were assayed. We observed significant differences in both hormone levels and hormone-body mass index (BMI) correlation between tasters and non-tasters. Tasters had higher plasma levels of leptin (p=0.05), tumor necrosis factor-α (TNF-α) (p=0.04), and Insulin-like growth factor 1 (IGF-1) (p=0.03). There was also a trend towards increased IGF-1 levels in the saliva of tasters (p=0.06). We found a positive correlation between plasma levels of glucose and BMI (R=0.4999, p=0.04) exclusively in non-tasters, not in tasters. In contrast, plasma C-peptide levels were found to be positively correlated to BMI (R=0.5563, p=0.03) in tasters. Saliva TNF-α levels were negatively correlated with BMI in tasters (R= -0.5908, p=0.03). Our findings demonstrate that there are differences in circulating levels of leptin, TNF-α and IGF-1 between tasters and non-tasters. These findings indicate that in addition to regulate eating behaviours, taste perception could also affect energy metabolism by controlling hormone secretion. People with different taste sensitivity may respond differently to the nutrient stimulation. Further work investigating the link between taste perception and peripheral metabolic control could potentially lead to the development of novel therapies for obese control.